Neuroprotection and Functional Recovery Associated with Decreased Microglial Activation Following Selective Activation of mGluR2/3 Receptors in a Rodent Model of Parkinson's Disease - Hugh Chan; Helen Paur; Anthony C. Vernon; Virginia Zabarsky; Krishna P. Datla; Martin J. Croucher; David T. Dexter (Parkinson's Disease)
Clinical trials have demonstrated positive proof of efficacy of dual metabotropic glutamate receptor 2/3 (mGluR2/3) agonists in both anxiety and schizophrenia. Importantly, evidence suggests that these drugs may also be neuroprotective against glutamate excitotoxicity, implicated in the pathogenesis of Parkinson's disease (PD). However, whether this neuroprotection also translates into functional recovery is unclear. In the current study, we examined the neuroprotective efficacy of the dual mGluR2/3 agonist, 2R,4R-4-aminopyrrolidine-2,4-dicarboxylate (2R,4R-APDC), and whether this is accompanied by behavioral recovery in a rodent 6-hydroxydopamine (6-OHDA) model of PD. We now report that delayed post lesion treatment with 2R,4R-APDC (10 nmol), results in robust neuroprotection of the nigrostriatal system, which translated into functional recovery as measured by improved forelimb use asymmetry and reduced (+)-amphetamine-induced rotation compared to vehicle treated animals. Interestingly, these beneficial effects were associated with a decrease in microglial markers in the SNc, which may suggest an antiinflammatory action of this drug.